2003
DOI: 10.1152/japplphysiol.01115.2002
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous capillary recruitment among adjoining alveoli

Abstract: . Heterogeneous capillary recruitment among adjoining alveoli. J Appl Physiol 95: 469-476, 2003; 10.1152/ japplphysiol.01115.2002.-Pulmonary capillaries recruit when microvascular pressure is raised. The details of the relationship between recruitment and pressure, however, are controversial. There are data supporting 1) gradual homogeneous recruitment, 2) sudden and complete recruitment, and 3) heterogeneous recruitment. The present study was designed to determine whether alveolar capillary networks recruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In all positions, vertical gradients of perfusion were observed, although multiple stepwise linear regression analysis revealed that both gravity and geometry of the vascular tree influenced regional blood flow. Further complexity is added by heterogeneity in blood flow even between neighboring groups of alveoli, as shown by Baumgartner et al (39). Consideration of these factors has led to the proposal of a refined model of lung zones (217,219) whereby all three zones can exist within the same horizontal (isogravimetric) plane, but the numbers of different zones within each plane shifts with increasing hydrostatic pressure down the lung, from predominantly zones 1 and 2 at the apex to all zone 3 conditions in the dependent lung regions.…”
Section: Effects Of Respiration On Blood Flowmentioning
confidence: 99%
“…In all positions, vertical gradients of perfusion were observed, although multiple stepwise linear regression analysis revealed that both gravity and geometry of the vascular tree influenced regional blood flow. Further complexity is added by heterogeneity in blood flow even between neighboring groups of alveoli, as shown by Baumgartner et al (39). Consideration of these factors has led to the proposal of a refined model of lung zones (217,219) whereby all three zones can exist within the same horizontal (isogravimetric) plane, but the numbers of different zones within each plane shifts with increasing hydrostatic pressure down the lung, from predominantly zones 1 and 2 at the apex to all zone 3 conditions in the dependent lung regions.…”
Section: Effects Of Respiration On Blood Flowmentioning
confidence: 99%
“…All animals were handled according to guidelines established by the National Institutes of Health and Institute of Laboratory Animal Resources. The protocols were based on techniques previously developed in our laboratory (3,4,6,36,37,38,39,40,41,42,43) and extended by others who studied the pulmonary microcirculation in vivo (2,5,20,21,22,29,30,33,34).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the detection of edema formation, IVM has also been used extensively to characterize the processes of capillary recruitment and derecruitment (not to be confused with alveolar R/D discussed above). IVM studies in mechanically ventilated rabbits or dogs or isolated rat lungs have demonstrated the considerable potential for capillary recruitment in the pulmonary vasculature at high perfusion rates or pressures (Wagner, 1988;Hanson et al, 1989;Kuhnle et al, 1995;Baumgartner et al, 2003), respectively. Importantly, this topic has recently gained considerable translational attention since several clinical studies of pulmonary hemodynamics at rest and during exercise in healthy resting supine subjects suggest that most of the pulmonary microvasculature is already recruited at baseline.…”
Section: Intravital Microscopy For Analysis Of Alveolar Perfusion Gamentioning
confidence: 99%